Pengaruh Model Pembelajaran PoE terhadap Keterampilan Berpikir Kritis pada Materi Koloid Siswa Kelas XI di SMA IT Granada - Sefi Dwi Wahyuni; Muhammad Amir Masruhim; Sukemi Sukemi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Students' critical thinking skills in colloid material are still low, possibly due to a lack of problem-solving abilities. Therefore, the application of various learning models is considered necessary, one of which is Problem-Based Learning (PoE). This study aims to investigate the impact of PoE on students' critical thinking skills at Granada Polytechnic (SMA IT Granada) in colloid material. A quasi-experimental design and quantitative experimental methods were used. Fifty students from grades 11 A and B were selected as research subjects through census sampling. A post-test control design was used. Data collection used post-test data as primary data, supplemented by observation sheets of student classroom activities. The results showed that the average post-test score of the experimental group was 78, while the average post-test score of the control group was 59. The t-test results showed that the hypothesis Ha was true, therefore, it can be concluded that the application of the PoE model at Granada Polytechnic can improve students' critical thinking skills in colloid material.